1993
DOI: 10.1055/s-2006-959596
|View full text |Cite
|
Sign up to set email alerts
|

Feverfew and Vascular Smooth Muscle: Extracts from Fresh and Dried Plants Show Opposing Pharmacological Profiles, Dependent upon Sesquiterpene Lactone Content

Abstract: Preparations of fresh or dried feverfew (Chrysanthemum parthenium) are widely consumed in the U.K. as a remedy for arthritis and migraine, but the pharmacological basis for this has not been established. We have, therefore, compared the properties of extracts of fresh plants with those of dried powdered leaves available commercially from health food shops. The two extracts differed radically in their content of alpha-methylbutyrolactones and in their pharmacological profile when tested in vitro on the rabbit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Recent studies showed that extracts of fresh leaves contain sesquiterpene xmethylenebutyrolactones such as parthenolide which cause irreversible, time-dependent and non-specific inhibition of aortic smooth muscle contractility (Barsby et al, 1992;. In contrast, extracts of dried powdered leaves available from health food shops do not inhibit aortic contractility and do not contain m-methylenebutyrolactones (Barsby et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that extracts of fresh leaves contain sesquiterpene xmethylenebutyrolactones such as parthenolide which cause irreversible, time-dependent and non-specific inhibition of aortic smooth muscle contractility (Barsby et al, 1992;. In contrast, extracts of dried powdered leaves available from health food shops do not inhibit aortic contractility and do not contain m-methylenebutyrolactones (Barsby et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 5-HT 1B and 5-HT 1D receptors are considered to be the main molecular targets of sumatriptan and congeners in acute treatment, 44 45 whereas 5-HT 2A and 5-HT 2C receptors are targeted by 5-HT antagonists, such as methysergide, oxetorone, pizotifen and cyproheptadine, which are used in migraine prophylaxis. [46][47][48] The mechanism of action of TAN is not well understood, but 5-HT receptor-blocking properties have been reported, [49][50][51][52] and inhibition of binding to 5-HT 2A and 5-HT 2C receptors, and to a lesser extent 5-HT 1B receptors, 53 has been suggested to play a role. There are several limitations to our study that deserve consideration.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in the blood pressure was accounted for as a secondary action due to the effect on the heart muscle, and on the respiratory center. More recently the sesquiterpene lactone parthenolide has been demonstrated to interfere markedly with both contractile and relaxant mechanisms in vascular smooth muscle (64,65).…”
Section: Biological Activities Of Arnica Sesquiterpene Lactonesmentioning
confidence: 99%